Collective ethics of resistance: The organization of survival in the Warsaw Ghetto. (November 2019) - Courpasson, David; Marti, Ignasi
This article aims to shed light on how 'powerless' people can organize to survive in situations of mass oppression. Research on powerlessness often explains compliance and political inaction by a culture of silence, generated from the sedimentation of numerous experiences of defeat. We question this assertion by drawing from an illustration of certain inhabitants of the Warsaw Ghetto, who managed to create a micro-society and reclaim the social relations the Nazis sought to destroy. Building on the work of Schaffer, we explain these collective ethics of resistance as the view that people should actively participate in the creation and maintenance of their own social relations. Through this lens, we argue that ethics and resistance are intertwined.